A Rare Incidence of Poland’s Syndrome in a Female Child: A Case Report - Bist, Aayush; Bhandari, Nirajan; Kanodia, Piush; Chaulagain, Pratima (Journal of Nepalgunj Medical College, 2023)
Poland’s syndrome is a rare condition characterized by the underdevelopment or absence of chest muscles on one side of the body and malformation of the hand and arm. This condition affects males more frequently than females and its cause is still unknown. The diagnosis is usually made in childhood, but in some cases, it may not be evident until adolescence or adulthood. Treatment options include surgical reconstruction and prosthetic devices to improve arm and hand function and appearance. While this syndrome can have a significant impact on a person’s physical and emotional well-being, early intervention and appropriate management can lead to improved quality of life. In our case it was an accidental finding in a 7 months old female with severe pneumonia for whom conservative management was done. We are interested in reporting this case because of its rare presentation, so cases would not get missed by the treating clinician.